SENSOR TCS3200 UNTUK MENDETEKSI PEMILIHAN WARNA BUAH KOPI BERBASIS XBEE PRO - ana, Sarj; Hesti, Emilia (POLITEKNIK ANIKA, 2018)
Lots of inventions as well as all the uses of technological advances that are very helpful in alleviating human work, especially in the field of industry that cultivate fruit crops with small size. This paper provides a method of accelerating use of TCS3200 color sensors for color quantization, it was done with various images and showed that the modifications have been able to show that the TCS3200 color sensor is also very competitive as the color quantization of images, both in terms of effectiveness and efficiency. On the other hand, this system will use the pattern by knowing the coffee grouping control system with wireless signal using Xbee pro module, where the XBee Proo module is to set the remote control with wireless network assisted, so the farmers do not have to bother to controling from close range. Furthermore, the data base will be built for several colors of fruit coffee and the comparison of fruit shape to be made with a control system grouping the fruit of coffee will be done using servo motors, so that when the tool works will be in line with the use of color sensors that can detect the color of the coffee beans. Key words : Mikrokontroler Arduino, Sensor dan Transducer, Sistem Embeded, Xbee Pro